AMPA Induces NO-Dependent cGMP Signals in Hippocampal and Cortical Neurons via L-Type Voltage-Gated Calcium Channels. (11th November 2019) - Giesen, Jan; Füchtbauer, Ernst-Martin; Füchtbauer, Annette; Funke, Klaus; Koesling, Doris; Russwurm, Michael
Abstract: The nitric oxide (NO)/cGMP signaling cascade has an established role in synaptic plasticity. However, with conventional methods, the underlying cGMP signals were barely detectable. Here, we set out to confirm the well-known NMDA-induced cGMP increases, to test the impact of AMPA on those signals, and to identify the relevant phosphodiesterases (PDEs) using a more sensitive fluorescence resonance energy transfer (FRET)-based method. Therefore, a "knock-in" mouse was generated that expresses a FRET-based cGMP indicator (cGi-500) allowing detection of cGMP concentrations between 100 nM and 3 μM. Measurements were performed in cultured hippocampal and cortical neurons as well as acute hippocampal slices. In hippocampal and cortical neurons, NMDA elicited cGMP signals half as high as the ones elicited by exogenous NO. Interestingly, AMPA increased cGMP independently of NMDA receptors and dependent on NO synthase (NOS) activation. NMDA- and AMPA-induced cGMP signals were not additive indicating that both pathways converge on the level of NOS. Accordingly, the same PDEs, PDE1 and PDE2, were responsible for degradation of NMDA- as well as AMPA-induced cGMP signals. Mechanistically, AMPAR induced calcium influx through L-type voltage-gated calcium channels leading to NOS and finally NO-sensitive guanylyl cyclase activation. Our results demonstrate that in addition to NMDA also AMPA triggers endogenous NO formation and hence cGMP production.